RESEARCH ON THE POTENTIAL USE OF USING SENSORS TO MEASURE AIR IMPURITIES - Немченко, Юрій; Кучменко, Олександр (SWorldJournal, 2025)
The paper addresses the issue of the presence and negative impact of impurities in the air on human safety and health. The sources of pollution and existing approaches to assessing air pollution levels are analyzed. It is noted that modern electronic com